The Influence of Participative Leadership, Proactive Personality and Knowledge Sharing on Innovation Work Behavior in The Creative Industry - Krisanti, Krisanti; Anindita, Anindita (International Journal of Science, Technology & Management, 2025)
The purpose of this research is to explore how Participative Leadership, Knowledge Sharing, and Proactive Personality influence Innovative Work Behavior in employees who are graduates from creative industries in Jakarta. The research was conducted on 154 respondents who met the research criteria, by distributing questionnaires online. The data processing method uses SEM PLS. The research results show that Participative Leadership has an influence on Knowledge Sharing. However, Participative Leadership has no effect on Innovative Work Behavior. Proactive Personality has an influence on Knowledge Sharing, Proactive Personality has an influence on Innovative Work Behavior, and Knowledge Sharing has a role that can influence Innovative Work Behavior in employees.